Combustion Characteristics Of A Diesel- Hydrogen Dual Fuel Engine - Santoso, W. B.; Ariyono, S. (2010)
Among the alternative fuels, hydrogen shows great potential in the near future. In the present study, hydrogen utilization as diesel engine fuel was investigated. Hydrogen can not be used directly in a diesel engine due to its autoignition temperature higher than that of diesel fuel. One alternative method is to use hydrogen in enrichment or induction. To investigate the combustion characteristics of this dual fuel engine, a single cylinder diesel research engine was converted to utilize hydrogen as fuel. Hydrogen was introduced to the intake manifold using a mixer before entering the combustion chamber. The engine was run at a constant speed of 2000 rpm and variable loads. At each load step the flow rate of hydrogen was varied. Fuel consumption, injector needle lift movement, and cylinder pressure were measured. Introducing hydrogen to the combustion chamber reduced the diesel fuel consumption. Indicated efficiency slightly increases with hydrogen enrichment at 15 Nm load. At lower load the efficiency decreases. Specific energy consumption increases with increase in hydrogen flow rate at 5 and 10 Nm load. Inversely, it decreases at higher load. Cylinder pressure decreases with hydrogen enrichment at 5 and 10 Nm, but slightly increases at higher load